Examination of different wall jet and impinging jet concepts to produce large-scale downburst outflow - Mejia, Alvaro Danilo; Elawady, Amal; Vutukuru, Krishna Sai; Chen, Dejiang; Chowdhury, Arindam Gan (Frontiers in Built Environment, 2022)
Thunderstorm downburst winds are a major cause of severe damage to buildings and other infrastructure. The initiative of the NSF-NHERI Wall of Wind (WOW) Experimental Facility to design and develop a downburst simulator was established to open new horizons for multi-hazard engineering research by extending the current capabilities of the facility to enable the simulation of non-synoptic winds. Five different downburst simulator designs have been tested in the 1:15 small-scale replica of the WOW to identify the optimal design. The design concepts tested herein considered both the 2-D impinging jet and the 2-D wall jet simulation methods. The basic design methodology consists of transforming the available atmospheric boundary layer (ABL) wind simulator into downburst winds by adding an external modification device to the exit of the flow management box. A flow characterization comparison among the five contending downburst simulators, along with comparisons to real downbursts and previous literature findings, has been conducted. The study on the effect of surface roughness length on the height of the peak wind velocity showed that the implementation of a 2-D plane wall jet enables large-scale outflows (higher peak velocity height) with high Reynold numbers, which is advantageous in terms of reducing scaling effects. In general, the current research work showed that four downburst simulation methods were suitable for adoption; however, only one downburst simulator was recommended based on the feasibility of construction in the facility. The chosen downburst simulator consisted of a two louver slat system near the bottom, with a blockage at the top. This configuration enables producing a large rolling vortex passing through the testing section, which would serve adequately in the further study of turbulent flow characterization and testing of larger scale test models.